PEMANFAATAN TECHNOLOGY ENHANCED LEARNING (TEL) DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA SMA - Allifa, Dini; Arianto, Jumili; Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student learning outcomes are influenced by various complex factors, ranging from learning interest and the school environment to the accuracy of material transformation strategies in the classroom. Field phenomena indicate that the low mastery of Pancasila Education materials often stems from a lack of active student involvement in a one-way learning process. One of the primary causes of this condition is the dominance of conventional methods that have not optimized the integration of digital technology as an interaction medium. This study aims to analyze the influence of implementing the Technology Enhanced Learning (TEL) method on the learning outcomes of Pancasila Education among 11th-grade students at SMAN 4 Pekanbaru. The research method used is quantitative with a Pretest-Posttest Control Group Design. The research sample consisted of 80 students divided into experimental and control classes. Data were collected through tests, observation, and documentation. The results of the Independent Sample T-Test showed that (5.701 > 1.991), indicating a significant effect of the TEL method implementation. Based on the N-Gain test, the experimental class obtained a score of 0.67 (medium category), outperforming the control class which was in the low category. This study concludes that the TEL method can create a more interactive and effective learning atmosphere in improving student learning outcomes compared to conventional approaches.